Nanoscale biocompatible structures generated from fluorinated tripodal phenylenes on gold nanoprisms - García-Castro, Miguel; Moscoso, Ana; Sarabia-García, Francisco Ramón; López-Romero, Juan Manuel; Contreras-Cáceres, Rafael; Díaz-Morilla, Amelia (Wiley, 2022)
Modification of gold substrates with a stable, uniform and ultrathin layer of biocompatible materials is of tremendous interest for the development of bio-devices. We present the fabrication of hybrid systems consisting of triangular prism gold nanoparticles (Au@NTPs) covalently covered with tripod-shaped oligo(p-phenylenes) featuring trifluoromethyl groups. Their synthesis is accomplished using a biphenyl boronic ester as the key compound. Au@NTPs were prepared through a seedless procedure using 3-butenoic acid and benzyldimethyl ammonium chloride, and modified with aminothiol groups. Coverage of this amine-modified gold substrate with a self-assembled monolayer (SAM) of tripod-shaped molecules is carried out in ethanolic solution. The hybrid system avoids up to 70 % of protein corona formation, and allows unspecific attachment for bulky adsorbates, providing an optimal biosensing platform. Chemical composition and morphology are analyzed by transmission electron microscopy (TEM), UV-visible spectroscopy and field emission scanning electron microscopy (FESEM).
Keywords: Oro; Nanoscale; Tripodal phenylenes; Gold nanoprism